Faktor-Faktor Yang Mempengaruhi Permintaan Listrik Rumah Tangga Di Kabupaten Pemekaran Dalam Provinsi Jambi - Saiyid Syekh (Universitas Batanghari Jambi, 2021)
Electricity resources are one of the important factors in supporting the economic and social development of society (human resources). This is proven still not optimal utilization of electricity in The Expansion Regency (Tebo). This study aims to analyze the factors that affect household electricity demand in Expansion District in Jambi Province, for this first step of study in Tebo Regency. Using a quantitative approach supported by qualitative approach, which selected 100 respondents in a Proforsional Stratifide Random Sampling. Based on regression methods using SPSS found the result that the average income of the family (X1), the Number of Family Members (X2) and the Number of Power Tools (X3) both together (over all test) and partially significantly influence to household electricity demand (Y). Therefore, it is necessary to synergize the government, private and the community to meet the electricity needs in Tebo Regency.